Molecular modelling of four penicillins: bencylpenicillin, phenoxymethylpenicillin, ampicillin and amoxicillin - Elso Manuel Cruz Cruz; Eslhey María Sánchez Domínguez (Medisur)
Background:Penicillins differ structurally among themselves by the lateral chains. At the same time, they have differences in their pharmacological action that can be associated to modifications included in the betalactamic ring and/or effects localized in the same chains. Making it clear would be a contribution to the search of the most adequate structural and electronic characteristics to design better penicillins. Objective:To compare structural properties, density of the atomic charges and the frontier orbitals of four penicillins: bencylpenicillin, phenoxymethylpenicillin, ampicillin and amoxicillin. Method:The molecular structures were optimized with PM3 semiempirical calculi. The molecular properties were calculated according to the Density Functional Theory, at a B3LYP/6-31G(d) level. The density of the atomic charges and the frontier orbitals were analyzed. The effect of the substituents on the properties of the betalactamic ring was evaluated. Results: The structural parameters of the betalactamic ring do not change as consequence of the modifications in the lateral chain linked to carbon 6. The ring has a marked tendency to planarity. There are no variations in the density of the positive charge of the carbonylic carbon. Conclusions: The structures and electronic properties of the betalactamic ring, structural basis of these antibiotics, do not have significant modifications among modelled penicillins.